The Influence of the COVID-19 Pandemic on the Imports and Exports in China, Japan, and South Korea - Wei, Panpan; Jin, Cheng; Xu, Chen (Frontiers in Public Health, 2021)
In this paper, time-series and cross-country data spanning from January to December, 2020 are adopted to empirically investigate the impact of COVID-19 pandemic on export and import among China, Japan and South Korea. In the models, industrial production, trade openness, government response (including monetary and fiscal intervention) and the pandemic impact of major trade partners are controlled. In addition to the whole sample, three sub-samples, which are China, Japan and South Korea, are also estimated in consideration of their distinctive characteristics. The results of the study show that domestic epidemics in China, Japan and South Korea have a non-significant (statistically significant) effect on imports, but are negatively correlated with Japan in terms of exports; epidemics in major trading partners are negatively correlated with imports in Japan and positively correlated with exports in China and South Korea; and government intervention is positively correlated with imports in China and positively correlated with exports in China, Japan and South Korea.